The meaning of liberal education. Issue 1 (2014) - ,
Abstract : Purpose – The purpose of this essay is to comment on the philosophy of liberal education and its structure; the goal of general education and how it fulfills the goals of liberal education; and the four key elements of liberal education, including the "liberating" aspects of general education, the need for an emphasis on questions more than on answers, the meaning of a global perspective, and the connections of each of the above to extracurricular experiences and engaged citizenship. Design/methodology/approach – This essay is a review of the topics of liberal and general education, their components, and their importance. Findings – Using the design and methodology mentioned above as a way to explore the purpose, the essay reveals selected universal truths about a liberal or "liberating" undergraduate education. Research limitations/implications – The approach that is detailed can be assessed in comparison to other formulations of liberal and general education. Practical implications – The framework described above suggests possibilities for redesigning liberal and general education programs so as to have a greater impact on undergraduate student learning and to foster experiential and interdisciplinary learning. Originality/value – While this is a personal perspective based on many decades of senior positions in higher education, it is based not only on the author's own analysis and thinking, but also on a broad understanding of the literature about these topics.